2018
DOI: 10.1016/j.celrep.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Brain Shuttle Antibody for Alzheimer’s Disease with Attenuated Peripheral Effector Function due to an Inverted Binding Mode

Abstract: Receptors show promise for the transport of monoclonal antibodies (mAbs) across the blood-brain barrier. However, safety liabilities associated with peripheral receptor binding and Fc effector function have been reported. We present the Brain Shuttle-mAb (BS-mAb) technology, and we investigate the role of Fc effector function in vitro and in an Fcγ receptor (FcγR)-humanized mouse model. Strong first infusion reactions (FIRs) were observed for a conventional mAb against transferrin receptor (TfR) with a wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 38 publications
1
64
1
Order By: Relevance
“…We have previously shown that the BS technology allows efficient delivery of antibodies to the brain. [7,18] We propose that this enhanced brain delivery is a direct consequence of the monovalent engagement of the BS construct with the highly expressed TfR on the brain endothelium. On this basis we genetically fused a rat selective OX26 anti-TfR antibody to hNEP.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the BS technology allows efficient delivery of antibodies to the brain. [7,18] We propose that this enhanced brain delivery is a direct consequence of the monovalent engagement of the BS construct with the highly expressed TfR on the brain endothelium. On this basis we genetically fused a rat selective OX26 anti-TfR antibody to hNEP.…”
Section: Plos Onementioning
confidence: 99%
“…Based on other studies utilizing a species-selective mouse anti-TfR antibody (8D3) and the rat selective OX26, it is most likely that the sFab OX26-NEP construct gains access to the CNS by TfR-mediated transport at the BBB. There is some evidence of TfR expression at the choroid plexus [18] and iron transport across the blood-CSF barriers which makes it possible that transport of sFab OX26-NEP through the choroid plexuses may also account for some of the construct-related activity in the CSF. The brain exposure of a TfR BS in vivo is not only affected by efficiency of transcytosis across the BBB but also by its plasma halflife.…”
Section: Plos Onementioning
confidence: 99%
“…The common mechanism of transcytosis of varying MTHs across the abluminal membrane is also debated, and it is clear that antibodies against the TfR may differ based on their affinity for the TfR. Both high-and low-affinity, as well as monovalent and bivalent TfR antibodies have been engineered, and these different antibodies for the same TfR may warrant different success rates of entry into the brain parenchyma (Niewoehner et al 2014;Yu et al 2011;Weber et al 2018;Hultqvist et al 2017;Chang et al 2018). Some studies suggest that TfR antibodies with high affinity can be trapped within the brain vasculature due to their high affinity, which prevents their transportation across the abluminal side of brain capillaries (Yu et al 2011).…”
Section: (Iv) Bbb Receptor Mediated Transport Of Epomentioning
confidence: 99%
“…Several studies have demonstrated increased CNS exposure to therapeutic antibodies by combining them with RMT targeting antibodies against the transferrin receptor, insulin receptor, low-density lipoprotein receptor-related proteins 1 and 2, and the large neutral amino acid transporter 1 [911]. However, challenges exist in optimizing antibody properties (such as affinity, valency, bispecific format, and Fc receptor engagement) to effectively and safely traffic across the brain endothelium [1216]. Improved in vitro models that enable further research of the cellular and molecular mechanisms underlying transcytosis at the BBB are needed to improve these CNS drug delivery technologies [14, 17, 18].…”
Section: Introductionmentioning
confidence: 99%